Development of e-assessment system for laboratory practical test : E-pratesim / Zadariana Jamil ... [et al.] - Jamil, Zadariana; Mohd Saim, Noraida; Othman, Zulhafizal (Universiti Teknologi MARA Cawangan Pahang, 2019)
The development of e-assessment system of laboratory practical exam/test for Civil Engineering Diploma students is presented. The conventional laboratory practical exam requires lecturers to be on-site or in campus to make the assessment for their students. This new approach provides a broad access for a lecturer who is not able to attend the conventional laboratory exam at the laboratory and on the scheduled time. Furthermore, the e-PraTeSiM system also allows:- (i) the enhancement of practical exam assessment standard due to the mechanism used in the system; and (ii) the improvement of digital student record. This system is simple, flexible and user friendly. The implementation of this system was done, firstly, by recording or lives streaming of the student who is doing the practical exam in the laboratory. Then, the student was asked with some questions provided in the system and his/her answer was recorded. The body gesture and voice level of the student were recorded in the system and used to evaluate the level of psychomotor and affective domains of the students that are included in the Outcome Based Education (OBE) requirements. Thus, the overall assessment for the student can be done efficiently and accurately. This system also includes a QR code for each student, displaying their results and performance individually. This data will be included in the student digital record as a reference for lecturers and future employers (for student). This system is an evolution of practical test assessment that fulfils the vision and mission of UiTM towards Industrial Revolution (IR4.0).